(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Tourism is not new concept it’s old as man civilization. Tourism has the potential to restore, protect and promote local heritage and communities, but can diminish and destroy both when improperly developed. Over the last few years, tourism has played a very important role in the economic development of many countries. Tourism industry is one of the leading job creators and also one of the rapidly growing sectors. India is a land of great tourism potential. From north Kashmir to south Kanyakumari, from east Arunachal Pradesh to west Gujarat, every region has its own uniqueness and flavor - be it coldhot desert, rivers, forests, islands each landform bound to mesmerize tourists. The Ministry of Tourism is the nodal agency for the development and promotion of tourism in India and maintains the Incredible India campaign. Tourism and hospitality creates diversified employment opportunities in different fields like accommodation, food and beverage establishment, transportation services, travel agencies etc, and the challenges are poor pay and working conditions, sexual harassment, discrimination, unequal treatment, low education and training, seasonality and political instability which drastically reduce the number of visitors which in turn brings high employees’ turn over.